1994
DOI: 10.1346/ccmn.1994.0420504
|View full text |Cite
|
Sign up to set email alerts
|

Surface Diffusion: Is It an Important Transport Mechanism in Compacted Clays?

Abstract: Abstract--Surface diffusion, or migration within the electrical double layer next to mineral surfaces, is often invoked as a significant contributor to the overall diffusion coefficient in compacted clays, particularly where model predictions underestimate measured diffusion coefficients. The potential for surface diffusion of Sr 2 § Ca 2+ and Na + on three clays compacted to dry bulk densities of 1.25 and 1.60 Mg/m 3 was examined. The clays were a bentonite, an illite/smectite, and a glacial lake clay (compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…Surface diffusion has been reported for Cs + in smectite clays (17,18), and Sr 2+ in smectites and granite (17)(18)(19). On the other hand, the results of Oscarson (15) indicate that surface diffusion has a relatively minor contribution for Sr 2+ , Ca 2+ , and Na + transport in smectite. To our knowledge, no studies have been published that evaluate the significance of U(VI) surface diffusion in soils.…”
Section: Diffusionmentioning
confidence: 99%
“…Surface diffusion has been reported for Cs + in smectite clays (17,18), and Sr 2+ in smectites and granite (17)(18)(19). On the other hand, the results of Oscarson (15) indicate that surface diffusion has a relatively minor contribution for Sr 2+ , Ca 2+ , and Na + transport in smectite. To our knowledge, no studies have been published that evaluate the significance of U(VI) surface diffusion in soils.…”
Section: Diffusionmentioning
confidence: 99%
“…These properties are of interest in chemistry of colloids and fields such as material, geophysical, and environmental sciences (3)(4)(5)(6)(7). In this paper, the transport of ions in a representative elementary volume (REV) of a granular porous material is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the surface diffusion hypothesis can explain the observed salinity dependence of D e . However, Oscarson 3) and Choi and Oscarson 9) reported that there was no positive relationship between K d and D e for a different type of bentonite media. As they also used the through diffusion system with circulation, there are probably other explanations for the observed differences.…”
Section: Resultsmentioning
confidence: 96%
“…2(a)), tracer and tracer-free solutions were circulated individually in the porous plastic filter on each side of the specimen. The flow rate controlled by the tube pump was several cm 3 per h. A membrane filter (pore size 0.22 µm, ca. 0.1 mm in thickness) was placed between the porous filter and bentonite to restrict the leaching of bentonite during the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation